Proper treatment of scalar and vector exponential potentials in the Klein-Gordon equation: Scattering and bound states - Aquino Curi, Elvis J.; Castro, Luis B. [UNESP]; de Castro, Antonio S. [UNESP] (Springer Nature, 2019)
We point out a misleading treatment in the literature regarding bound-state solutions for the s-wave Klein-Gordon equation with exponential scalar and vector potentials. Following the appropriate procedure for an arbitrary mixing of scalar and vector couplings, we generalize earlier works and present the correct solution to bound states and additionally we address the issue of scattering states. Moreover, we present a new effect related to the polarization of the charge density in the presence of weak short-range exponential scalar and vector potentials.